THE RELATIONSHIP BETWEEN EFFECTIVE FAMILY COMMUNICATION AND PERSONAL HYGIENE IN THE ELDERLY IN JATIMAKMUR BEKASI CITY - Maharani, Afifa Rizqia; Indrawati, Lina; Baltasar S. S. Dedu (Rena Cipta Mandiri, 2025)
A person who is in the elderly phase experiences changes both physically and mentally and socially. Physical changes include decreased physical strength, stamina and appearance. In Indonesia, it has not been supported by improving the quality of health care for the elderly. Knowledge about elderly care, both by family, parents themselves and other social institutions is still very inadequate. The factors that cause lack of self-care in the elderly are due to lack of knowledge or cognitive deficits. The application of effective communication in the family is a form of interaction between children and elderly parents which has implications for personal hygiene. The method that will be used by the researcher is quantitative with an analytical research design. The design of this study was cross sectional with the technique of Probability Sampling simple random sampling. The population in this study were 85 elderly and after entering into the Slovin formula, a sample of 70 elderly people was obtained. The results of statistical analysis using the chi-square test obtained a p-value of 0.000 0.05. This shows that Ha is accepted and Ho is rejected. It was obtained from the bivariate result that 63 (90.0%) respondents had good effective family communication with good personal hygiene. Based on the results of the study, there is a significant relationship between effective family communication and personal hygiene in Jatimakmur, Bekasi City.